Gloss on the Judgment of the Higher Court of Lawyers (Anwaltsgerichtshof) of the Land of North Rhine-Westphalia of 11 November 2015, Case 1 AGH 23/15 - Thierjung, Eva-Maria (Studia Prawa Publicznego, 2025)
The gloss refers to a judgment of the Higher Court of Lawyers (Anwaltsgerichtshof) of North Rhine-Westphalia Land of 11 November 2015 (1 AGH 23/15), in which the Court ruled upon the decision of a bar association to revoke the permission to use the professional title of “Fachanwalt” (specialist lawyer) due to a breach of the professional obligation to undergo compulsory continuing professional development. The Court correctly recognized that, firstly, the Bar had made its decision on the wrong basis and, secondly, that there was nevertheless no reduction of its discretion to zero, since despite the existence of the reason for revocation – at least in this specific case – discretion still had to be exercised by the Bar. In this way, the Court corrected the Bar’s doubly erroneous decision. The law applicable in this case has been reformed since the decision with the aim of harmonizing the way the bars use their discretion by issuing decisions concerning the revocation of permissions to use the title “Fachanwalt” – the harshest sanction in this context. By these means, erroneous decisions such as the one at hand shall be minimized. However, the new regulation is also fraught with uncertainty and the extent to which it will provide a remedy will only be- come apparent with time.